vault backup: 2025-02-09 16:30:33
This commit is contained in:
parent
5039193ffd
commit
50e775cf43
@ -108,7 +108,13 @@ $$ \dfrac{d}{dx} e^x = e^x $$
|
|||||||
$$ \dfrac{d}{dx}a^x = a^x*(\ln(a)) $$
|
$$ \dfrac{d}{dx}a^x = a^x*(\ln(a)) $$
|
||||||
for all $a > 0$
|
for all $a > 0$
|
||||||
|
|
||||||
|
# Trig Functions
|
||||||
|
|
||||||
|
## Sine
|
||||||
|
$$ f'(x) = \lim_{h \to 0} \dfrac{\sin(x + h) - sin(x)}{h} $$
|
||||||
|
Using the sum trig identity, $\sin(x + h)$ can be rewritten as $\sin x \cos h + \cos x \sin h$.
|
||||||
|
|
||||||
|
This allows us to simplify, ul
|
||||||
# Examples
|
# Examples
|
||||||
|
|
||||||
> Differentiate $f(x) = 4\sqrt[3]{x} - \dfrac{1}{x^6}$
|
> Differentiate $f(x) = 4\sqrt[3]{x} - \dfrac{1}{x^6}$
|
||||||
|
Loading…
x
Reference in New Issue
Block a user